1996
DOI: 10.1038/383453a0
|View full text |Cite
|
Sign up to set email alerts
|

A new group of conserved coactivators that increase the specificity of AP-1 transcription factors

Abstract: The Jun proteins are nuclear proteins that combine with Fos proteins to form a gene-regulatory protein, AP-1. They have highly conserved DNA-binding and dimerization domains, resulting in almost identical sequence-recognition properties. Nevertheless, there are many indications that each Jun protein activates a distinct and only partially overlapping set of AP-1 target genes. Using the more variable activation domain of c-Jun as a bait, we identified a protein, JAB1, that interacts with c-Jun and JunD, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
378
2
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(392 citation statements)
references
References 27 publications
9
378
2
3
Order By: Relevance
“…A direct e ect of USF on Jun homodimers also seems unlikely, since several results (this paper and data not shown) failed to detect any interaction between the two proteins. One possible explanation could be that USF interferes with a ternary factor such as CBP or the recently reported JAB1 factor (Arias et al, 1994;Claret et al, 1996), resulting in the observed drop of Jun activity. Additional experiments are required to further investigate this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…A direct e ect of USF on Jun homodimers also seems unlikely, since several results (this paper and data not shown) failed to detect any interaction between the two proteins. One possible explanation could be that USF interferes with a ternary factor such as CBP or the recently reported JAB1 factor (Arias et al, 1994;Claret et al, 1996), resulting in the observed drop of Jun activity. Additional experiments are required to further investigate this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…In this respect, it is interesting that the related gene encoding OBF1 is most highly expressed in young meristematic regions of leaves (Singh et al, 1990). Transcriptional activation probably requires interaction with other factors, one possibility being the proteins binding to the neighbouring octomer motif conserved in many histone promoters, another being heterodimerization with other members of the bZIP protein family and yet another being binding to co-activators to increase bZIP activation specificity (Claret et al, 1996). The pattern of bZIP910 and bZIP911 gene expression shows a reasonably good correlation to expression of the gene encoding histone H4 in Antirrhinum inflorescences (Forbert et al, 1994) although post-transcriptional regulation may further modify the amount of each transcription factor active in any one cell.…”
Section: Which Genes Are These Proteins Regulating?mentioning
confidence: 99%
“…1 Subsequent studies found that Jab1 is also the fifth component of the COP9/signalosome complex. 2,3 Recently, a new biological function of Jab1 has been suggested.…”
mentioning
confidence: 99%